2013
DOI: 10.5551/jat.16824
|View full text |Cite
|
Sign up to set email alerts
|

The Apolipoprotein B/A1 Ratio is Associated with Reactive Oxygen Metabolites and Endothelial Dysfunction in Statin-Treated Patients with Coronary Artery Disease

Abstract: Aim:The prognostic significance of the apolipoprotein B/A1 (ApoB/A1) ratio in statintreated patients with coronary artery disease (CAD) is unknown. We aimed to evaluate the association of the ApoB/A1 ratio with oxidative stress and endothelial dysfunction in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…There are several mechanisms might explain the increased risk of PTB among women with higher serum ApoB level or ApoB/ApoA-1 ratio. Previous studies have revealed a positive association between ApoB level and oxidative stress 36 . Elevated level of oxidative stress during pregnancy is related to higher risk of PTB 37 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There are several mechanisms might explain the increased risk of PTB among women with higher serum ApoB level or ApoB/ApoA-1 ratio. Previous studies have revealed a positive association between ApoB level and oxidative stress 36 . Elevated level of oxidative stress during pregnancy is related to higher risk of PTB 37 .…”
Section: Discussionmentioning
confidence: 93%
“…Elevated level of oxidative stress during pregnancy is related to higher risk of PTB 37 . Furthermore, both experimental 38, 39 and epidemiological studies 36,40 have reported that elevated ApoB level or ApoB/ApoA-1 ratio was associated with endothelial damage. Chen et al 41 reported that impaired endothelial function was present in women with preterm delivery.…”
Section: Discussionmentioning
confidence: 97%
“…The apo B/apo A1 ratio is a typical marker for the atherogenic /antiatherogenic condition, and a higher apo B/apo A1 ratio represents progression in the atherosclerotic state. Previous studies have suggested that a high apo B/apo A1 ratio strongly correlates with pathophysiological markers of atherosclerosis defined by coronary angiography [ 8 , 20 ], and calcium scores of the coronary arteries [ 21 ], and by ultrasound techniques such as the thickness of carotid arteries [ 16 , 22 , 23 ], endothelial dysfunction [ 24 ] and existence of femoral plaques [ 25 ]. In addition, a high apo B/apo A1 ratio can also be used to predict risk of carotid plaque development [ 26 ] and major adverse cardiovascular events [ 14 , 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a general belief that an important anti-atherogenic substance, Apolipoprotein A1 (ApoA1), is considered as in case of High-Density Lipoprotein (HDL), enters into the vascular wall from the vascular lumen to act against atherosclerosis by mediating reverse cholesterol transport [1][2][3].…”
Section: Introductionmentioning
confidence: 99%